Perencanaan dan Pengendalian Persediaan Bahan Baku serta Komponen Mbox di PT. X - Alif nurul hidayah (Jurnal Penelitian Enjiniring, 2019)
The development of the industrial now increasingly rapid because the companies compete each other to be excellent in their fields. Companies can survive in the midst of competition if the company is able to increase efficiency. One of the way is to control inventory. This research was conducted to make the planning and control of the optimal needs of raw material and component at PT. X by applying the Wagner Within Algorithm method to achieve the Mbox production target. Types of raw materials and component in forming one Mbox product unit consist 18 types of component and 6 types of raw materials. Data processing will be done by setting the Mbox request every period. After that, inventory control costs are calculated using the 3 step Wagner Within Algorithm method. From the calculation results obtained by order lot size which results in a total inventory cost of Rp. 54.109.030. with component production every period must be fulfilled and raw material ordering is done at the beginning of the period to meet the production needs to entire period. Except for 1,5 mm steel plate order, which are ordered 6 times. The difference is due the calculation results from the Wagner Within Algorithm method which requires bookings made at certain periods.